Analysis of soil nailing using finite element method - Teoh Khai Ying (School of Environmental Engineering, University Malaysia Perlis, 2014)
Soil nailing system is always well known preventive method in slope improvement. Soil nailing is a complex system that requires detailed analysis to ensure stability. In the past, slope stability has always been limited in using limit equilibrium (LE) method. LE method developed based on slices concept along the potentially sliding block. Due to certain complications, finite element (FE) method is slowly replacing LEM in geotechnical application.